Knowledge-based safety training system (KBSTS): A prototype implementation - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 1994)
A computer-based safety training system for process operators must be able to make effective presentation of textual material, test the trainee's understanding through quizzes and facilitate plant simulation. The general framework of such a system is presented in an earlier paper (Computers in Industry, Vol. 17, 1991, pp. 349–358). In this paper, we discuss the development and implementation of a prototype Knowledge-Based Safety Training System based on the framework. The design philosophy, system architecture and the plant modelling methodology are described.